A COMPARATIVE STUDY ON EFFECTIVENESS OF OPEN VERSUS CLOSED KINETIC CHAIN EXERCISES TO IMPROVE GAIT IN SPASTIC DIPLEGIC CEREBRAL PALSY (International Journal of Physiotherapy, 2016)
Background: Cerebral Palsy (CP) describes a non- progressive but not unchanging disorder of movement and posture due to an insult to or anomaly of the developing brain. People with spastic diplegia typically walk slowly and have difficulties in performing activities such as walking running or jumping. Children with spastic diplegic cerebral palsy are relied more on cadence to increase speed. Hence, the purpose of this study is to compare the effectiveness of open and closed kinetic chain (OKC and CKC) exercises in improving gait in spastic diplegic cerebral palsy.Methods: 30 children with spastic diplegic cerebral palsy of both genders with age 4-12 years was taken. Cadence and distance covered in 1Minute Walk Test was calculated before and after the test. The intervention for group A was CKC exercises and group B was OKC exercises for 3 days a week for 6 weeks and each session lasted for 30-45 minutes was given for both the groups.Results: Paired t-test was performed to find effectiveness of CKC and OKC improving gait in spastic diplegic CP to see the difference of means of 1minute walk, t = 10.789 which is significant (p = 0.000) and for cadence, t = 3.37 which is highly significant (p = 0.00) implying that cadence and distance covered in1minute walk was more with CKC exercises.Conclusion: Based on the result it is concluded that CKC exercises are effective in improving gait than OKC exercises in spastic diplegic cerebral palsy.